Lung Cancer: Nebulized Gadolinium‐Based Nanoparticles: A Theranostic Approach for Lung Tumor Imaging and Radiosensitization (Small 2/2015). Issue 2 (January 2015) - Dufort, Sandrine; Bianchi, Andrea; Henry, Maxime; Lux, François; Le Duc, Géraldine; Josserand, Véronique; Louis, Cédric; Perriat, Pascal; Crémillieux, Yannick; Tillement, Olivier; Coll, Jean‐Luc
<x xml:space="preserve">Abstract</x> The direct administration of Gadolinium‐based theranostic nanoparticles (USRPs) into the airways is described on page 215 by J.‐L. Coll and co‐workers. This work enables the deposition of USRPs around tumor nodules, their multimodal detection (fluorescence and MRI) and, due to the USRPs' radiosensitizing properties, augments significantly the impact of radiotherapy and consequent survival. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>